The Effectiveness of Augmentative and Alternative Communication Application Implementation in Improving Student with Autism Verbal Communication - Nurul Aina Nazri; Aliza Alias (Department of Special Education, 2018)
Augmentative and Alternative Communication is widely used in the educational context as a learning aid for improving verbal communication among students. The aims of this research are to study the effectiveness of Augmentative and Alternative Communication implementation in improving students with autism verbal communication. This research was conducted at one of the primary school in Machang, Kelantan. 2 students with autism participate in this study as a respondent and divided into treatment group and controlled group. Pre and post-tests were conducted to collect and analyze data. Finding in this research shows there was a significant difference between the pre and post-test score in the treatment group when Augmentative and Alternative Communication application was implemented in the intervention.